Ace takes flight - McCarthy, Cory (McCarthy, Cory. B.E.S.T. world., 2021)
Following in the footsteps of his older brother Finn, eleven-year-old Ace Wells enters the Biological Enhancement Systems Technology (B.E.S.T.) program where he'll train to master a biological augmentation known as SuperSoar, a set of wings that allow people to fly. Initially, Ace finds it hard to make friends and adjust to the school's rigid rules--not to mention learning to fly the tricky technology. Soon, however, those problems take a back seat to the disappearance of a new friend and his suspicions that something nefarious is going on at the school.